KAJIAN POTENSI LANSKAP DI DAERAH PERSAWAHAN UNTUK PENGEMBANGAN OBJEK WISATA DI KOTA BINJAI - Liana Rizky Marantika; Fariz Harindra Syam (Jurnal Arsitektur ARCADE, 2023)
Abstract: Binjai City is a level II city area with the status of.a municipality within the province of North Sumatra, Indonesia. Binjai is located about 22 Km west of the provincial capital of North Sumatra. Binjai City is divided into 5 districts, namely Kota Binjai, North Binjai, South Binjai, West Binjai, East Binjai. Binjai is one of the cities that has a large rice field area. Binjai City is also one of the tourist cities that is currently very often visited by many people. This study aims to landscape development to analyze the development of potential landscapes in rice fields as a means of developing tourist attractions in binjai city. Based on the questioner research 73% respondent strongly agreed and 27% agreed to lanctioning rice fields as tourism object.The results of this activity are in the form of design designs for educational areas about planting rice fields, outbound, relaxing areas, playgrounds, and supporting facilities. The excavation of information from the villagers was also welcomed and added to the enthusiasm of the residents to make East Binjai a tourist village. The results of the Park Tourism design can help for development even though it is carried out in stages.Keyword: Agrotourism, Binjai City, LandscapeAbstrak: Kota Binjai merupakan kawasan kota tingkat II yang berstatus kotamadya di dalam provinsi Sumatera Utara, Indonesia. Binjai terletak sekitar 22 Km sebelah barat ibu kota provinsi Sumatera Utara. Kota Binjai terbagi menjadi 5 kabupaten yaitu Kota Binjai, Binjai Utara, Binjai Selatan, Binjai Barat, Binjai Timur. Binjai merupakan salah satu kota yang memiliki areal persawahan yang luas. Kota Binjai juga merupakan salah satu kota wisata yang saat ini sangat sering dikunjungi banyak orang. Penelitian ini bertujuan pengembangan lanskap untuk menganalisis pengembangan potensi lanskap di persawahan sebagai sarana pengembangan daya tarik wisata di kota binjai. Berdasarkan penelitian kuesioner 73% responden sangat setuju dan 27% setuju untuk menjadikan sawah lanctioning sebagai objek wisata.Hasil dari kegiatan ini berupa desain desain untuk area edukasi tentang penanaman sawah, outbond, area santai, taman bermain, dan fasilitas penunjang. Penggalian informasi dari warga juga disambut baik dan menambah semangat warga untuk menjadikan Binjai Timur sebagai desa wisata. Hasil rancangan Taman Wisata dapat membantu untuk pengembangan meskipun dilakukan secara bertahap.Kata Kunci : Agrowisata, Kota Binjai, Lanskap